Predictors of parental mediation in teenagers' internet use: a cross-sectional study of female caregivers in Lahore, Pakistan - Sarosh Iqbal; Rubeena Zakar; Florian Fischer (BMC, 2021)
Abstract Background The internet has become the most widely used medium among teenagers, who spend much of their time online, which raises parental concerns. Notwithstanding teens' increased internet use and exposure to online risks, little is yet known about parental internet mediation in local settings. The present research aimed to assess the various dimensions of parental mediation to regulate teens' use of the internet and their predictors. Methods A cross-sectional survey was conducted in the district of Lahore, Pakistan, among mothers/female caregivers of teens (aged 13-19 years). Only women were interviewed because they are more frequently engaged as primary caregivers than fathers or male caregivers. Furthermore, only qualified and working mothers from the top two professions among women, i.e. academia and medicine, were interviewed. A stratified random sampling technique was adopted, and 347 mothers were interviewed using face-to-face interviews at 11 universities and 11 hospitals/medical colleges. Data were entered and analysed using descriptive, bivariate and multivariate logistic regression analyses. Results The findings highlighted that more than 65% of respondents applied highly active mediation of internet safety, around 60% used highly active co-use mediation and more than 56% applied restrictive mediation. In addition, 36% of respondents monitored and 15.3% technically mediated to regulate their teens' use of the internet. The results of the multivariate logistic regression revealed that the majority of respondents were more inclined to adopt active internet safety mediation if they had teens aged 16-19 years, with medium internet addiction, possessed good digital skills, felt confident about their teens' coping appraisal to perform online protection, and considered their teens to have high self-esteem and resilience. Conclusions This research found that parental internet mediation is a multifaceted concept used to regulate teens' online activity and enhance a resilient approach to reduce the risks associated with use of the internet. The researchers recommend developing parental guidelines, e-safety resource material, local support networks and community programmes to educate parents, teachers and teens in order to raise awareness and promote resilient pathways amongst teens.